EFFECT OF INFLATION AND PRICE INDEX ON EQUITY ASSETS - Dalimunthe, Ibram Pinondang; Lestari, Ajeng Desni (Universitas Pamulang, 2019)
The purpose of this study is to determine the effect of inflation and the equity price index on the net asset value of the Islamic Fixed Income Mutual Funds registered with the Financial Services Authority for the period from from 2011 to 2016. The type of search used is associative search. The data in this study are secondary historical data using Net Asset Value (NAV) and the share price index published by the Financial Services Authority (OJK), as well as inflation data published by Bank Indonesia for the period 2011-2016. The method used in this study uses regression analysis with panel data. The results show that inflation has a negative and significant impact on the net asset value. The equity price index has a positive and significant influence on the net asset value. Inflation and the equity price index simultaneously have a significant effect on the net asset value of Sharia mutual funds.